O12.2 Partnership context and consistent condom use among young african american men. (14th July 2019) - Craig-Kuhn, Megan Clare; Schmidt, Norine; Gomes, Gérard; Scott, Glenis; Watson, Shannon; Lederer, Alyssa; Kissinger, Patricia
Abstract : Background: Young African American (AA) heterosexual men have high rates of sexually transmitted infections (STIs). Consistent condom use effectively prevents STIs, but condom use decisions are made in the context of individual sexual relationships. This analysis describes partnership characteristics and condom use among young AA men. Methods: AA men aged 15–24 who lived or spent most of their time in New Orleans, Louisiana and had vaginal sex in the past 2 months were screened at non-clinical venues for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) using nucleic acid amplification testing. Men provided information on sexual partnerships including perception of risk behaviors on an audio computer-assisted self-interview. Generalized estimating equation is used to fit a marginal model to account for multiple partnerships. Results: Participants (n=1152) reported characteristics of 1733 partnerships. In partnerships where condoms were not always used, men were more likely to be committed to the partner (47% vs 28%, p<0.01), plan to have sex with her again (72% vs 56, p<0.01), able to re-contact her (87% vs 78, p<0.01), already have a child (11% vs 3%, p<0.01), financially support her (27% vs 20%, p<0.01), and feel closer to her (median 8 vs 6, p<0.01), compared to partnerships where condoms were always used. Men not always using condoms were also more likely to have sex while drunk/high (52% vs 31%, p<0.01). Rates in men were 10% for CT and 1% for GC; men with CT and/or GC were less likely to always use condoms (44% vs 60%, p<0.01) compared to men negative for CT and/or GC. Conclusion: STI rates are high, especially for those in partnerships where condoms are not always used. Consistent condom use is lower in committed, closer partnerships, suggesting that prevention interventions should focus on condom use among this group. Disclosure: No significant relationships.